How do Visit Facilitation and Accessibility of Prisons Relate to Visits from Professionals and Volunteers? - Pasma, Amanda (Crime & delinquency, 2024)
Reintegration support by community-based professionals and volunteers (CBPs) is needed to prepare prisoners for release. Yet, the way in which CBPs are received, informed and accommodated, may hamper in-prison involvement. Therefore, the current study explores the visit facilitation and accessibility of prisons in the Netherlands as experienced by CBPs. A new instrument to measure facilitation and accessibility across institutions is introduced. The findings among 4,309 prisoners and 1,077 professionals across 24 Dutch prisons revealed that although institutions differ in facilitation and accessibility, this is unrelated to prison visits received from most CBPs, apart from the likelihood of receiving visits from parole officers. The study confirms the importance of considering facilitation and accessibility in relation to in-prison involvement of external agencies.